"Bringing Our Small, Imperfect Stones to the Pile": The Everyday Work of Building a More Just World. Issue 2 (May 2023) - Battle, Brittany Pearl; Nopper, Tamara K; Randolph, Antonia
In this conversation between Brittany Pearl Battle and Tamara K. Nopper (facilitated by Antonia Randolph), two sociologists who have been involved in a variety of social justice struggles (e.g. prison abolition, worker's rights, Asian American rights), describe the everyday practices that make up struggles for social justice. They identify a spectrum of practices that individuals can do to bring about a more just world, while arguing that all practices towards justice do not constitute organizing or activism. Moreover, they describe the salience of their status as workers and women of color as structuring the ways they have pursued social change at different points in their lives. In so doing, they identify academia as a workplace rather than being an academic as a status as the salient force that shapes how they work to build a more just world. Ultimately, the article questions the usefulness of the designation scholar-activist, opting to recognize the unique role of activists in social change while affirming that we all bring what we can to struggles for justice.